Gender Differences in Body Image, Body Mass Index and Dietary Intake among University Students. - Yi Ling Lee; Shi-Hui Cheng (Pertanika Journal of Social Sciences & Humanities, 2020)
Body image dissatisfaction has shown to play a role in weight control and leads to an imbalance of energy and nutrient intakes. This study aims to determine gender differences in body image and its association with Body Mass Index (BMI) and dietary intakes among university students. A total of 100 university students were recruited. Body image was assessed by Body Shape Questionnaire and Figure Rating Scale. Dietary intake was assessed by meal practices and 3 days of dietary recall. All statistical data were analysed by SPSS. About 80% of females wished to be thinner and 28% of males wished to be fatter. The prevalence of body image dissatisfaction in this study was 89%. Participants who were dissatisfied with their body image had a significantly higher body image concern (mean score 82.24 ± 27.17) than body image satisfied group (59.64 ± 13.28). There was a significant positive correlation between BMI and body shape questionnaire score (r = 0.306; p = 0.002). The mean BMI in the body image dissatisfied group (22.07 ± 3.53 kg/m²) was significantly higher than the satisfied group (20.97 ± 1.27 kg/m²). Females who had body image dissatisfaction seldom snack whereas females who had satisfied body image always snack in between meals. There were gender differences in energy and nutrient intakes. Majority of the students did not meet the Malaysian Recommended Nutrient Intakes (RNI). The findings highlight the need for nutrition interventions with a focus on weight management and healthy eating patterns to promote positive body image among university students.